Zambia - Country Economic Memorandum : Policies for Growth and Diversification, Volume 1. Main Report - World Bank (Washington, DC, 2013)
In October 1991 Zambia moved to a multiparty democratic system. In the following years, the government implemented a number of policy and structural reforms, liberalizing exchange and interest rates, simplifying the tariff structure, and removing quantitative restrictions on trade, privatizing most state-owned enterprises, and substantially withdrawing from the agriculture sector. Despite these reforms, economic growth has remained lackluster, and poverty and social conditions have worsened. There are however, hopeful signs that increased growth and poverty reduction are within reach in Zambia. The country's economy has long been tied to the copper industry, whose purchasing power has been in decline for decades. But declining copper prices were not the only reasons Zambia's economic performance declined between 1991 and 2002. Excluding the one-time disruption in real sector activity in 1994-95, real GDP grew at an average annual rate of 3 percent during 1991-2002. The report argues that estimates puts its annual long-term growth potential at about 5 percent, implying per capita income growth of 2.5-3.0 percent a year, and, the reason why its potential is not being achieved, lies in several key problems, namely macroeconomic mismanagement, lack of ownership of reform and poor policy implementation, a weak investment climate, lack of good governance, and, the HIV/AIDS pandemic. And further asserts that central to the lack of macroeconomic stability - in particular to the high inflation and real interest rate - is the lack of fiscal control and commitment to fiscal discipline. Zambia's large external and rising domestic debt, combined with budgetary dependence on external financing, has constrained the government's ability to exert monetary control to achieve macroeconomic stability. The financial sector must become more efficient and capable of supporting private investment and growth. Key institutional and policy issues for immediate attention are creating a mechanism to resolve the debt of failed banks and state-owned non-bank financial institutions; upgrading the human and technological resources of financial system regulators and supervisors; improving access to financial services, in particular rural financial services; and, investing in financial system infrastructure to improve market data, and accounting and auditing standards. The report expands on the country's opportunities in the mining sector, particularly copper, but also on its rich reserves of gemstone minerals, as an opportunity for export diversification; in the manufacturing sector, specifically textiles, garments, and processed foods; and, in tourism development.